The Implementation of the Seven-Rights Procedure in Drug administration in a Hospital Inpatient Room: the Inhibiting Factors and Alternative Solutions - Puspitasari, Shinta Dwi; Dewanto, Aryo; Holipah, Holipah Holipah; Muliawan, Arrasyid Indra (Fakultas Kedokteran Universitas Brawijaya)
Medication error becomes one of the main concerns in ensuring patient safety worldwide. In the first semester of 2020, Hospital X reported two incidents of medication error. Although the incidents were categorised as â€œadverse eventâ€ and â€œnear missâ€, it should have been prevented. One of the methods to prevent medication error is the application of the seven-rights procedures in drug administration. This study aims to identify the inhibiting factors in the implementation of the seven-rights procedure in X Hospital as well as to obtain alternative solutions to those inhibiting factors. This study used a cross-sectional design. The data was gathered from 20 nurses at Hospital X using a questionnaire to measure the knowledge, attitude, and behaviour of nurses on the seven-rights procedure. The data is also supported by observation on the actual implementation of the procedures. At the end of the data gathering process, interviews with nurses in inpatient room were conducted to obtain their opinion about the obstacles in applying the seven-rights procedures. The results show that the main problem of drug administration errors was the lack of standard operating procedures (SOP) and nursesâ€™ non-compliance behaviour on the seven-rights procedure. This study also reveals that there is no relationship between the nursesâ€™ knowledge and their behaviour in applying the seven-rights procedures. To prevent medication error, the hospital manager should revise the SOP, conduct a periodic internal refreshment-workshop about the procedure, and perform scheduled supervision to the nurses.